2012
DOI: 10.1111/j.1365-2613.2012.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen‐deficiency inducing haematopoiesis dysfunction via reduction in haematopoietic stem cells and haematopoietic growth factors in rats

Abstract: Haematopoiesis is a self-renewing and multi-directional differentiation process of haematopoietic stem cells (HSCs), which is modulated very precisely by the haematopoietic microenvironment in bone marrow. Our previous study has demonstrated that oestrogen-deficiency leads to haematopoiesis dysfunction which manifests as a decrease in haematopoietic tissues and an increase in adipose tissues in bone marrow. However, the mechanism involved in the oestrogen-deficiency effects on haematopoiesis dysfunction is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…This result is in accordance with our previous study in vivo (Qiu et al 2012). The exact mechanism of E2 on HSCs is still obscure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is in accordance with our previous study in vivo (Qiu et al 2012). The exact mechanism of E2 on HSCs is still obscure.…”
Section: Discussionsupporting
confidence: 93%
“…Nakada et al (2014) recently confirmed that estrogen increases the self-renewal of HSCs in females during pregnancy. In our previous study in rats, when estrogendeficiency was established by ovariectomy, hematopoiesis dysfunction occurred due to the decreased number of HSCs in the bone marrow (Qiu et al 2012). Further, a reduction of osteoblasts also occured, which positively correlated A.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Oestrogen also maintains the number and activity of HSCs in bone (Qiu et al 2012), and increases the ratio of OPG/RANKL (Yan & Ye 2015).…”
Section: Endocrine Effects In Bonementioning
confidence: 99%